Communist Politics in Ireland 1916-1945 : Volume 1: Pursuit of the Workers' Republic in the Post-Connolly and Larkin Era, 1916-1928 - Milotte, Mike, (Historical Materialism Book Series ;, 2025)
Mike Milotte's clear and meticulous reconstruction of Irish communism in the 1920s leaves no stone unturned. He reassesses the communist movement and its key figures in light of previously overlooked or misinterpreted material from the Comintern archives. During the revolutionary era, Roddy Connolly's Communist Party robbed banks to fund its activities, and 20-year-old Connolly engaged in gun-running for the IRA while struggling to maintain control of his fractious party. In a later period of retreat, James Larkin refused to submit to the 'imperialistic' British Communist Party or follow the dictates of Moscow's Stalinist bureaucracy, resisting its policies and practices on instinct.